Pengenaan Pajak Bumi dan Bangunan Bagi Pemukiman Terapung di Atas Perairan Indonesia - Hermawan, Rio; Michael, Tomy (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Houses as a means of survival and a place for the development of community life in water areas, so houses are very needed by people who live in water areas, so that people in that area build floating houses on the water. This research aims to analyse the regulations related to the existence of floating houses that are not covered in the Law of the Republic of Indonesia Number 28 of 2009 concerning Local Taxes and Regional Retribution. Therefore, what is meant is professional building materials that are installed in full or are in the process of being installed on land, in water, and in the sea. Based on this definition, large houses and their structures that are still submerged in water are included in the category of Taxable Goods according to Law No. 28/2009 concerning Regional Taxes and Regional Retribution. The selection of this type of study is based on the lack of clarity of land tax regulations and floating settlement buildings above Indonesian waters, because the existence of floating houses is on the water and in the sea. This research uses normative research methods through the UU approach contained in related laws and regulations along with existing norms and developing in society. The existence of floating houses in Indonesia has existed since the Dutch colonial era. Floating houses are spread in several provinces in Indonesia, such as Sulawesi, Kalimantan, and Palembang. This floating house stands with a construction system planted on water controlled by the state.